A propos de la décision chez A. Badiou ou peut-on être atheiste: По повод одлуката кај А. Бадју или дали може да се биде атеист - Riha, Jelica; Popovska, Elisaveta (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Jelica Riha | Јелица Риха Title (French): A propos de la décision chez A. Badiou ou peut-on être atheiste Title (Macedonian): По повод одлуката кај А. Бадју или дали може да се биде атеист Translated by (French to Macedonian): Elisaveta Popovska | Елисавета Поповска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 39-57 Page Count: 18 Citation (French): Jelica Riha, “A propos de la décision chez A. Badiou ou peut-on être atheiste,” Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006): 39-57. Citation (Macedonian): Јелица Риха, „По повод одлуката кај А. Бадју или дали може да се биде атеист“, превод од француски Елисавета Поповска, Идентитети: списание за политика, род и култура, т. 5, бр. 1 (зима 2006): 39-57.